Analysis of Product Distribution Channels at PT Cipta Niaga Semesta Sumedang - Safitri, Putri Aliza; Kurniasih, Nining; Sumiati, Ai (Journal of Bussines Management Basic, 2025)
This study aims to examine the implementation of distribution channels, the challenges encountered, and the solutions undertaken at PT Cipta Niaga Semesta Sumedang. Using a qualitative method, data were collected through interviews, observations, and documentation. The results show that the distribution process runs fairly well through two channels: Zero Level Channel and One Level Channel. Inventory, warehouse, and transportation management are considered effective. However, challenges such as limited road access and uneven distribution coverage still persist. The company is advised to expand its distribution network, improve inventory management, optimize warehouse usage, and increase the number of delivery fleets.